Hygrothermal effects on dynamic mechanical snalysis and fracture behavior of polymeric composites - Costa,Michelle Leali (2005)
Polymer composites used above their glass transition temperatures Tg present a substantial degradation of physical properties; therefore a material's glass transition temperature and its change with moisture absorption are of practical importance. Little attention has been paid to the role of the adhesive bonding between the reinforcing fiber and matrix, particularly for BMI matrix. In this work the effect of moisture on the dynamic mechanical behavior and the fiber/matrix interface was investigated. Two systems were evaluated: carbon fabric/epoxy and carbon fabric/bismaleimide laminates. The results demonstrated that the moisture absorbed by the laminates causes either reversible or irreversible plasticization of the matrix. The humidity combined with the temperature effects may cause significant changes in the Tg matrix and toughness affecting the laminate strength. Moisture absorption was correlated to the fracture mode of the laminate demonstrating the deleterious effect of moisture on the interface. This leads to debonding between fiber and matrix. This behavior was investigated by scanning electron microscopy and dynamic mechanical analysis.